Occupational health (job dissatisfaction and work life balanced) impacted to poor sleep quality in nurse - Prasetyono, Juli Dwi; Permatasari, Henny; Setiawan, Agus; Mulyono, Sigit; Susanto, Tantut; Mansyur, Muchtaruddin (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Nurses constitute the largest proportion of healthcare human resources globally, accounting for 59% of all healthcare professionals worldwide. Poor sleep quality among nurses can lead to decreased performance, lack of concentration, physical and mental health issues, and a reduced quality of life. Purpose: To determine the impact of occupational health (job dissatisfaction and work-life balance) on poor sleep quality in nurses. Method: This study employed a quantitative cross-sectional design with purposive sampling. A total of 38 respondents participated in the study. The research instruments included Microsoft Forms, utilizing the Work-Life Balance (WLB) questionnaire and the Pittsburgh Sleep Quality Index (PSQI) to assess sleep quality. Results: A total of 92.1% of nurses experienced poor sleep quality, 57.9% WLB was unbalanced, and 76.3% were dissatisfied with their jobs. The results of the bivariate analysis using the chi-square test showed that the p value of WLB was 0.651 and job satisfaction was 0.015*. This indicates that WLB is not related to sleep quality in nurses, while job satisfaction is related to sleep quality in nurses. Conclusion: There is a significant relationship between nurses' sleep quality and job satisfaction, but no association with WLB. Suggestion: Strengthening job satisfaction among nurses should be carried out extensively through strategies such as mindfulness-based stress reduction interventions. These efforts aim to enhance job satisfaction and workplace resilience, enabling nurses to provide optimal patient care in healthcare settings. Keywords: Job Satisfaction; Nurses; Occupational Health; Sleep Quality; Work-Life Balance. Pendahuluan: Perawat merupakan sumber daya manusia (SDM) tenaga kesehatan yang paling banyak secara global sebesar 59% dari seluruh profesi kesehatan di dunia. Kualitas tidur yang buruk pada perawat dapat menyebabkan kinerja berkurang, tidak konsentrasi, gangguan kesehatan baik fisik, dan mental serta menurunkan kualitas hidup. Tujuan: Untuk mengetahui dampak kesehatan kerja (ketidakpuasan kerja dan keseimbangan kehidupan kerja) terhadap kualitas tidur yang buruk pada perawat. Metode: Penelitian kuantitatif desain cross-sectional dengan teknik purposive sampling. Sampel pada penelitian sebanyak 38 responden. Instrumen penelitian menggunakan Microsoft form dengan kuesioner Work-Life Balance (WLB) dan Pittsburgh Sleep Quality Index (PSQI) untuk mengukur kualitas tidur. Hasil: Sebanyak 92.1% perawat mengalami kualitas tidur yang buruk, WLB tidak seimbang 57.9%, dan tidak puas terhadap pekerjaannya sebanyak 76.3%. Hasil analisis bivariat menggunakan uji chi-square, menunjukkan bahwa p-value WLB sebesar 0.651 dan kepuasan kerja 0.015*. Hal ini menunjukkan bahwa WLB tidak berhubungan dengan kualitas tidur pada perawat, sedangkan kepuasan kerja berhubungan dengan kualitas tidur pada perawat. Simpulan: Terdapat hubungan yang signifikan antara kualitas tidur perawat dengan kepuasan kerja, tetapi tidak ada hubungan dengan WLB. Saran: Penguatan kepuasan kerja yang diberikan kepada perawat perlu dilakukan secara massif melalui strategi, seperti intervensi mindfulness-based stress reduction program. Hal ini sebagai upaya meningkatkan kepuasan kerja pada perawat dan penguatan resiliensi di tempat kerja agar dapat memberikan asuhan keperawatan yang maksimal pasien di pelayanan kesehatan. Kata Kunci: Kepuasan Kerja; Kesehatan Kerja; Kualitas Tidur; Perawat; Work-Life Balance.